INCREASING ENVIROMENTAL CARE ATTITUDES THROUGH THE OUTDOOR STUDY METHOD IN SCIENCE LEARNING AT SDN BEKTIHARJO VI - Ingke Joanna; Agung Setyawan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
A school environment that is maintained and cared for properly will create a beautiful and comfortable environment for student learning activities. Therefore, it is important to instill an attitude of caring for the environment in students so that they have a positive attitude towards their environment. The purpose of this research is to increase students' environmental care attitude through the outdoor study method in science learning at SDN Bektiharjo VI. The data collection method used is the method of observation, questionnaires, interviews, and documentation. The results of this study indicate that outdoor learning can increase the attitude of caring for the environment in fifth grade students at SDN Bektiharjo VI. This can be seen from the results of observations that show an increase in the number of students who are aware of caring for plants at school. In addition, it can also be seen from the average percentage per class, where in the pre-cycle the average score of the questionnaire shows 0% because students do not apply environmental care at all, then the percentage score increases to 81.81% in cycle I, and increases again to 93.54% in the second cycle.